Pengaruh Metode Bernyanyi terhadap Kemampuan Mengingat Siswa pada Pembelajaran Pendidikan Agama Islam di SDN Cangkuang 06 Kabupaten Bandung - Farida Nahwa Pirdausi; Dedih Surana; Helmi Aziz (Bandung Conference Series: Islamic Education, 2024)
Abstract. The study was conducted to examine the effect of the singing method on students' memory abilities and the effectiveness of the singing method in Islamic Education learning using a quantitative approach with a type of Quasi-Experimental Design and Nonequivalent Control Group Design. The research sample consisted of students from classes III A and C, selected using purposive sampling based on the results of the students' final assessments. The results indicate that: 1) The average score of students before the application of the singing method was 58.79 in the experimental class and 54.41 in the control class. 2) After the application of the singing method, the average score in the experimental class increased to 83.93, while in the control class that did not use the singing method, it became 58.97. This shows that the class using the singing method had higher results. 3) The t-test showed a calculated t-value of 10.316, which is greater than the critical t-value of 1.668, leading to the conclusion that the singing method has an impact on students' memory abilities. The n-gain test results showed an average student score of 0.636, which falls into the medium category, and a score of 63.65%, which is considered quite effective. The conclusion is that the singing method can optimize students' memory abilities and is quite effective for use with students.Top of FormBottom of FormTop of FormBottom of Form Abstrak. Penelitian ini dilakukan untuk menelaah pengaruh dari metode bernyanyi pada kemampuan mengingat siswa dan tingkat efektivitas metode bernyanyi dalam pembelajaran Agama Islam denganmenggunakan pendekatan kuantitatif dengan jenis Quasi Experimental Designs dan desain Nonequivalent Control Group Design. Sampel penelitian terdiri dari peserta didik kelas III A dan C, menggunakan teknik purposive sampling berdasarkan hasil Penilaian Akhir Siswa. Hasil nya menyatakan bahwa: 1) Nilai rata-rata siswa sebelum penerapan metode bernyanyi yaitu 58,79 pada kelas eksperimen dan 54,41 pada kelas kontrol. 2) Setelah penerapan metode bernyanyi, nilai rata-rata di kelas eksperimen meningkat menjadi 83,93, sedangkan di kelas kontrol yang tidak menggunakan metode bernyanyi menjadi 58,97. Ini menunjukkan bahwa kelas yang menggunakan metode bernyanyi memiliki hasil yang lebih tinggi. 3) Uji t menunjukkan nilai untuk t hitung 10,316 > t tabel 1,668, dengan ini dapat diambil kesimpulan bahwa adanya pengaruh metode bernyanyi terhadap kemampuan mengingat siswa. Hasil uji n-gain menunjukkan rata-rata skor siswa 0,636, yang berada dalam kategori sedang, dan nilai 63,65%, yang termasuk kategori cukup efektif. Kesimpulan nya bahwa metode bernyanyi ini dapat mengoptimalkan kemampuan mengingat siswa dan cukup efektif untuk diterapkan pada siswa.